Urban planning in a world of informal politics - Deuskar, Chandan (City in the twenty-first century book series., 2023)
"This book draws from multiple disciplines and uses mixed methods to explore how politicians in developing democracies provide urban land and services to the poor in exchange for political support, how this impacts urban growth, and how urban planners can try to be more effective in this challenging political context"--